Comparaing the effect of discision technique and micro osteo perforation technique on loss anchorage during two –step retraction(A Clinical Study) - محمد, روان; فادي خليل, (Latakia University Journal -Medical Sciences Series, 2023)
The aim: The purpose of this study was to investigate the efficacy of discision method in loss anchorage in comparison to the micro osteoperforation method in loss anchorage in two step retraction technique. Methods: A single-blinded, parallel-group randomized controlled clinical trial was conducted at the Department of Orthodontics at the University of Tichreen Dental School, Syria. The study involved 14 patients (3 males, 11 females) at the age of 16–27years (mean age: 19.15 years). The patients had class II division I malocclusion and were treated with fixed appliances using the two-step retraction technique. With an allocation ratio of 1:1, the participants were randomly assigned to either the mop group (n = 7) or the discision group (n = 7) .The patients were seen every 28 day and taken an impression to made a dental cast until complete space closer. the measurements were obtained from casts by using a digital bicoles. Results: There was statistical difference between mop group and discision group in loss anchorage(0.05>p)in first month.there was non statistical difference between between mop group and discision (P > 0.05) in rest months. Conclusions: This is the first clinical orthodontic study to comparison between discision technique and mop technique on loss anchorage . The mop seems to be more effective in reducing loss anchorage just in first month from retraction.